The Influence of Communication, Individual Characteristics, and Work Environment on Employee Performance at Bank Tabungan Negara Denpasar Branch Office - Dewa Ayu Utari Pramaitha; Kadek Rai Suwena; Rudi Irwansyah (MASI Mandiri Edukasi, 2026)
This study examines the influence of communication, individual characteristics, and the work environment on employee performance at Bank Tabungan Negara Denpasar Branch Office. The research aims to identify how each of these variables affects employee performance both partially and simultaneously. The population consisted of 128 employees, and a saturated sampling (total sampling) technique was applied, meaning all employees were included as the research sample. Data were collected through questionnaires and documentation, and analyzed using multiple linear regression with SPSS. The results show that communication (β = 0.275), individual characteristics (β = 0.510), and work environment (β = 0.190) each have a positive and significant effect on employee performance. The constant value obtained was 6.873. Simultaneously, all three independent variables also have a positive and significant influence on employee performance. Among the variables, individual characteristics have the strongest effect.